Predictors of Death for Hospitalized Patients with COVID-19 in the First Year of the Pandemic in Northern Brazil - A Retrospective Study - , Daniele Melo Sardinha; , Yan Corrêa Rodrigues; , Ana Lúcia da Silva Ferreira; , Karla Valéria Batista Lima; , Ricardo José de Paula Souza e Guimarães; , Luana Nepomuceno Gondim Costa Lima (Archives of Current Research International, 2023)
Objective: Identified predictors of death for hospitalized patients with COVID-19 in the First Year of the Pandemic in Northern Brazil. Methods: A longitudinal retrospective cohort study was carried out, using data from the Brazilian Ministry of Health's COVID-19 severe case and hospitalization notification forms, considering the period from January 1, 2020 to December 31, 2020. The extracted variables were related to the epidemiological profile and outcome of the disease. Data were analyzed using SPSS software, with chi-square test by contingency table, binary logistic regression, and survival analysis. Results: Those vaccinated against influenza were associated with survivors in univariate and multivariate analysis, as well as survival analysis. The predictors of lethality were invasive ventilation (OR 6.627; CI 5.780–7.597), other pneumopathy (OR 1.901; CI 1.439–2.510), dyspnea (OR 1.899; CI 1.737–2.076), immunodeficiency (OR 1.905; CI 1.493–2.431), hospitalized in ICU (OR 1.764; CI 1.588–1.959), chronic kidney disease (OR 1.753; CI 1.396–2.203), diabetes mellitus (OR 1.210; CI 1.108–1.321), and male sex (OR 1.198; CI 1.111–1.293). Conclusion: Those vaccinated against influenza were associated with survival; namely, they showed a lower risk of death in the regression and showed longer survival in the survival analysis, when compared to those who were not vaccinated. The lethality was higher than the other studies, while the predictors were similar. Evidencing that COVID-19 had more impact on deaths, which may be associated with the vulnerability factors of the region.